In Quest of a Legal Framework for Domestic Workers in Bangladesh - Sourav, Md. Raisul Islam (Journal of Malaysian and Comparative Law, 2014)
Bangladeshi domestic workers suffer from lack of legal protection. There are a lot of laws, but none can ensure the rights of the domestic workers separately. Albeit, the Constitution of the People’s Republic of Bangladesh guaranteed some rights of the domestic workers impliedly. However, domestic workers can seek redress under ordinary civil and criminal laws of Bangladesh. Nonetheless, they need some sort of special treatment, because they work in private place and in more vulnerable situation. In addition, the nature of their work is quite different from other traditional work sectors. There is no provision for their working hours, leave, minimum wages, holiday, maternity benefits etc. Though the ILO Convention No 189 has been adopted to ensure the rights of the domestic workers but Bangladesh is not a state party to the convention. Hence they need a new piece of legislation to protect their employment rights. This research paper aims to find out the lacunas of existing laws of Bangladesh and recommend to enact a new law in this regard.